Data Collection and Analysis in a Pan-European Electric Vehicle Fleet - O'MAHONY, MARGARET (My University, 2013)
Electric vehicles are expected to replace a significant portion of existing light vehicle fleets around the developed world over the coming decades. The technology offers several benefits both on environmental and user levels when compared to traditional combustion engines. As the cost of fossil fuels continue to rise and the price of electromobility drops, this method of transport will become more prevalent. Analysis of early stage electric vehicle usage will allow stakeholders to plan the policy and infrastructure needed to facilitate and manage large scale roll out of the technology. A large collection of electric vehicle fleets and infrastructure networks operating in several European regions are monitored for analysis. The authors present preliminary results showing charging infrastructure utilisation for a range of vehicle and charge point use cases. This initial analysis shows that the usage levels for public infrastructure are low, while home charging is responsible for the highest levels of charge consumption. Business use cases, both for charge points and vehicles are characterised by high levels of peak time activity. Private use vehicles and household charge points show a concentration of energy usage in the latter part of the day, with a considerable peak in the early evening. All use cases display several hours of inactivity during the night time, both for charge events and travel patterns, confirming the potential for managed charging to take advantage of periods of low demand for electric vehicle charging. The data highlights the need for pricing incentives to regulate charging behaviour.
92nd Annual Conference of the Transportation Research Board
PUBLISHED
Washington D.C.
Keywords: electric vehicles; pan european; charging behaviour; Smart & Sustainable Planet